Pathogenesis and genetic characteristics of novel reassortant low-pathogenic avian influenza H7 viruses isolated from migratory birds in the Republic of Korea in the winter of 2016–2017 - Yu-Na Lee; Sun-Ha Cheon; Eun-Kyoung Lee; Gyeong-Beom Heo; You-Chan Bae; Seong-Joon Joh; Myoung-Heon Lee; Youn-Jeong Lee (Emerging Microbes and Infections, 2018)
Abstract In this study, we characterized H7 subtype low-pathogenicity (LP) influenza A viruses (IAVs) isolated from wild bird habitats in the Republic of Korea from 2010 to early 2017. Through national surveillance, 104 H7 IAVs were isolated, accounting for an average of 14.9% of annual IAV isolations. In early 2017, H7 subtypes accounted for an unusually high prevalence (43.6%) of IAV detections in wild birds. Phylogenetic analysis revealed that all the viruses isolated in the winter of 2016–2017 fell within cluster II of group C, belonging to the Eurasian lineage of H7 IAVs. Notably, cluster II of group C included the H7 gene from the highly pathogenic H7N7 IAV that was detected in northeastern Italy in April of 2016. Through a gene-constellation analysis, the H7 LPIAVs that we isolated constituted ≥11 distinct genotypes. Because the viruses belonging to the genotypes G2.1 and G1 were observed most frequently, we compared the replication and transmission of representative viruses to these genotypes in specific-pathogen-free chickens. Notably, the representative G2.1 strain was capable of systemic replication and efficient transmission in chickens (as evidenced by virus isolation and histopathological examination) without any clinical signs except mortality (in one infected chicken). The efficient subclinical viral replication and shedding of the G2.1 virus in chickens may facilitate its silent spread among poultry after introduction. Given that wild birds harbor novel strains that could affect poultry, our results highlight the need for enhanced IAV surveillance in both wild birds and poultry in Eurasia.